2006
DOI: 10.1073/pnas.0606698103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers that distinguish human papillomavirus (HPV)-positive versus HPV-negative head and neck cancers in a mouse model

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a leading cause of cancer mortality worldwide. Recent reports have associated a subset of HNSCC with high-risk human papillomaviruses (HPVs), particularly HPV16, the same subset of HPVs responsible for the majority of cervical and anogenital cancers. In this study we describe a mouse model for HPV-associated HNSCC that employs mice transgenic for the HPV16 oncogenes E6 and E7. In these mice, E6 and E7 induce aberrant epithelial proliferation and, in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
158
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(169 citation statements)
references
References 45 publications
10
158
1
Order By: Relevance
“…The HPV types have also been grouped into mucosal or cutaneous types, based on their tropism for specific epithelial sites. Mucosal HPV types found preferentially in precancerous and cancerous lesions have been designated as 'high-risk' types and these include types 16,18,31,33,34,35,39,45,51,52,56,58,59, 66, 68, and 70. Mucosal HPVs found in benign genital warts and other non-malignant lesions are generally labeled as 'low-risk' types, the most important ones being HPV 6,11,42,43, and 44 [1,2].…”
Section: Human Papillomaviruses (Structure and Classification)mentioning
confidence: 99%
See 1 more Smart Citation
“…The HPV types have also been grouped into mucosal or cutaneous types, based on their tropism for specific epithelial sites. Mucosal HPV types found preferentially in precancerous and cancerous lesions have been designated as 'high-risk' types and these include types 16,18,31,33,34,35,39,45,51,52,56,58,59, 66, 68, and 70. Mucosal HPVs found in benign genital warts and other non-malignant lesions are generally labeled as 'low-risk' types, the most important ones being HPV 6,11,42,43, and 44 [1,2].…”
Section: Human Papillomaviruses (Structure and Classification)mentioning
confidence: 99%
“…In this model, K14E6 and K14E7 mice were crossed but E6 and E7 could only induce a suprabasal DNA synthesis in the oral cavity [49,50]. On the contrary, when the mice were treated with the oral carcinogen 4-nitroquinoline-noxide (4-NQO) in their drinking water as a co-carcinogen, the animals were dramatically more susceptible to carcinogenesis and developed tumors almost fully penetrant as compared to the low tumor incidence in the like-treated non-transgenic control group [51]. Subsequently, the same group showed that E7 is the dominant HPV oncoprotein in HNSCC, and they also reported that pRb/p107-deficient mice developed HNSCC as frequently as did HPV-16 E7 transgenic mice.…”
Section: Hpv and Head And Neck Cancer (Hnscc)mentioning
confidence: 99%
“…It is overexpressed in HPV-related SCC but is usually deleted or otherwise inactivated in non-HPV-related head and neck SCC [19,20]. p16 expression by immunohistochemistry approaches 100% in HPVpositive oropharyngeal carcinomas in some studies [5,11,21,22] and is indicative of transcriptionally-active HPV.…”
Section: Introductionmentioning
confidence: 99%
“…MCM2 (a member of MCM family) expression is found to be aberrant in laryngeal squamous epithelial lesions (54). In addition, MCM7 is identified as a useful biomarker for HPV-positive HNSCC (55). Our data indicate that miR-519A may act as a therapeutic biomarker for HNSCC by targeting the DNA replication associated protein MCM7.…”
Section: Discussionmentioning
confidence: 82%